“Contenido, calidad y dinámica de las fracciones orgánicas como indicadores de calidad de suelos bajo diferentes cambios de uso en Achupallas”. - Vargas Torres, Jefferson Mauricio (2020)
Moorlands are neotropical ecosystems, located between 3,000 and 4,000 m.a.s.l., with high water retention potential and storage of organic carbon (OC), which fulfill functions associated with the regulation of carbon and water cycles. The objective of this research was to study the stability of the aggregates and the carbon content associated with each of the fractions. In addition, the carbon stored in the different organic fractions was quantified Under moorland soils (Pa) and its replacement by Pasture (P) and Cultivation (Cu) in the parish of Achupallas. The study was carried out using a randomized block design with three replications, in soil samples extracted at a depth of 30 cm, in Andosol type soils. The distribution of aggregates by size to the stability of the water and the fractionation of the organic matter in each of the treatments was used. The aggregation-disruption index (ADI) was -0.005, when replacing moorland by grass occurs and -0.008 when replacing by crop occurs respectively. The results showed that under moorland soils have a higher concentration of carbon associated with aggregates (143.98) compared to pasture (135.10) and cultivation (128.20) gr C / kg respectively. It can be concluded that from the fractionation of organic matter, the carbon that is incorporated in under moorland soils contributes approximately 20% of carbon in the fraction of particulate organic matter, while in Under Cultivation and Pasture soils they only contribute between 12 and 14%.